A New Approach in Modifying Polymeric Coatings to Increase Corrosion Resistance Properties. (4th April 2013) - Toloei, Alisina; Atashin, Sanam; Bahrololoom, Mohammad Ebrahim
Abstract : In this study, carbon steel sheets were coated with a modified epoxy coating. The urea-modified montmorillonite clay nanoparticles were added to a DGEBA epoxy resin in different contents and then applied to the surfaces. The corrosion resistance of the coated samples was determined by electrochemical techniques (open circuit potential and linear polarization) in 3.5 wt% NaCl solutions at room temperature and 80°C. Electrochemical impedance spectroscopy (EIS) evaluated the properties of polymer-coated metals and their changes during the exposure to corrosive environments. Scanning electron microscopy (SEM) was used to characterize the coatings. An improvement of protective properties of epoxy coatings with an optimal percentage of the modified clay in comparison with pure epoxy was achieved.